Religion and gender equality: patterns of a confrontational relationship in the international setting - Karagiannopoulou, Chara (The Greek Review of Social Research, 2017)
This paper focuses on the polemics between the progressive and the conservative-patriarchal Transnational Advocacy Networks (TANs) within the framework of the UN World Conferences on Women. It consists of an effort to present the patterns of the confrontational intersection of women’s human rights and the various faith-based restrictions imposed on them in the late modern era. The focus will be mainly on three texts: The Program of Action (UNFPA, Cairo, 1994), The Beijing Platform for Action (Beijing, 1995), and The Rome Statute establishing the International Criminal Court (Rome, 1998). It also discusses recent developments regarding the relationship between gender equality and religion by taking into consideration the outcomes of the special sessions of the 23rd, 49th, 54th, and 59th UN General Assemblies known as Beijing +5, +10, +15 and +20. It is argued that organized religious systems set impediments on the way toward gender equality.